2012
DOI: 10.1002/hyp.9209
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and loads of dissolved xenobiotics and hormones in two small river catchments of different land use in Luxembourg

Abstract: Abstract:The investigation focuses on the analysis of dissolved sulfonamides, tetracyclines, analgesics, anticonvulsants and hormones in surface water. Runoff event and baseflow samples were analysed in two small river catchments of different land use in Luxembourg. For most of the flood events, similar pollutant loads to those transported during 1 day with average baseflow discharge were observed. The maximum contents during flood events and the event mean concentrations are controlled by preevent hydro-clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The second highest concentration of carbamazepine was 490 ng L −1 , reported from the experiments that were carried out at a small stream in Germany which is impacted by a sewage treatment plant (Kunkel and Radke, 2012). CBZ-ep (carbamazepine-10,11epoxide) was measured at a concentration of 1 ng L −1 in Luxembourg (Krein et al, 2013) and up to a level of 1670 ng L −1 in Spain (López-serna et al, 2012a). dh-hCBZ (10,11-dihydro-10hydroxycarbamazepine) was also quantified from 1.36 ng L −1 to 70 ng L −1 in Spain (López-Serna et al, 2012b).…”
Section: Psychiatric Treatment Drugs (Ptds)mentioning
confidence: 99%
“…The second highest concentration of carbamazepine was 490 ng L −1 , reported from the experiments that were carried out at a small stream in Germany which is impacted by a sewage treatment plant (Kunkel and Radke, 2012). CBZ-ep (carbamazepine-10,11epoxide) was measured at a concentration of 1 ng L −1 in Luxembourg (Krein et al, 2013) and up to a level of 1670 ng L −1 in Spain (López-serna et al, 2012a). dh-hCBZ (10,11-dihydro-10hydroxycarbamazepine) was also quantified from 1.36 ng L −1 to 70 ng L −1 in Spain (López-Serna et al, 2012b).…”
Section: Psychiatric Treatment Drugs (Ptds)mentioning
confidence: 99%
“…While surface and subsurface runoff are known to be the most important drivers of pesticide dislocation and contamination into surface waters, and therefore, of surface water contamination, only a few studies focused on the contribution of flood events to remobilization and translocation of contaminant loads. For example, Krein et al (2013) highlight the crucial importance of flood event observation in contaminant transport studies. The same picture can be seen for our data, where the loads of the selected pesticides were considerably higher during flood events.…”
Section: Pesticides In River Water Samplesmentioning
confidence: 99%
“…[1][2][3] Aside from providing data on the level of xenobiotics in Luxembourgish waters, these studies have also demonstrated that the presence of these chemicals are due to inputs from land use, accidental spillage, wastewater effluent, and long range transport. 1,[3][4][5][6] Other studies have reported the measurement of 14 pesticides and their transformation products (TPs) both in surface water and drinking water. 3,7 The Luxembourg Water Management Agency (Administration de la Gestion de l'Eau, hereafter AGE), in compliance with the European Union Water Framework Directive (WFD), monitors different organic contaminants in Luxembourgish surface water.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the previously reported presence of chemicals in Luxembourg's environment 2,[4][5][6][7] and the widespread use of chemicals in daily life, a large number of compounds could be considered as potential environmental pollutants in Luxembourg.…”
Section: Introductionmentioning
confidence: 99%